Analisis Perbandingan Kinerja Keuangan Sebelum Dan Selama Covid-19 Pada Perusahaan Subsektor Transportasi - Dyunita, Dyunita; Rahajeng, Enika (Politeknik Sawunggalih Aji, 2024)
This study aims to analyze the financial performance in the period before covid-19 (2019) and during covid-19 (2021) in transportation subsector companies listed on the Indonesia Stock Exchange, by analyzing the financial performance one year before covid-19 and during covid-19. The method of determining the sample by Purposive Sampling technique obtained by 15 companies with the availability of a complete report. The analysis technique used in this study is the T-test (Paired Sample T-Test). Based on the results of the analysis, it was found that financial performance measured by five financial ratios, namely Current Ratio, Return on Assets, Total Asset Turnover, Dept to Equity Ratio, and Pershare earnings, was no different during covid-19 and during covid-19.